2013
DOI: 10.1038/srep02975
|View full text |Cite
|
Sign up to set email alerts
|

Towards ultrahigh volumetric capacitance: graphene derived highly dense but porous carbons for supercapacitors

Abstract: A small volumetric capacitance resulting from a low packing density is one of the major limitations for novel nanocarbons finding real applications in commercial electrochemical energy storage devices. Here we report a carbon with a density of 1.58 g cm−3, 70% of the density of graphite, constructed of compactly interlinked graphene nanosheets, which is produced by an evaporation-induced drying of a graphene hydrogel. Such a carbon balances two seemingly incompatible characteristics: a porous microstructure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
391
4
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 566 publications
(414 citation statements)
references
References 51 publications
10
391
4
2
Order By: Relevance
“…5c,d), further suggesting that little restacking is occurring in the compressed HGF films. This can be attributed to the robust interlock of graphene sheets that allows mechanical compression to reduce the pore size without significantly modifying the stacking characteristics of graphene and its 3D interconnected porous structure 18 . Importantly, these compressed HGF films can exhibit excellent electrical conductivity of B1,000 S m À 1 , and are mechanically strong enough to be used as the EC electrodes directly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5c,d), further suggesting that little restacking is occurring in the compressed HGF films. This can be attributed to the robust interlock of graphene sheets that allows mechanical compression to reduce the pore size without significantly modifying the stacking characteristics of graphene and its 3D interconnected porous structure 18 . Importantly, these compressed HGF films can exhibit excellent electrical conductivity of B1,000 S m À 1 , and are mechanically strong enough to be used as the EC electrodes directly.…”
Section: Resultsmentioning
confidence: 99%
“…Although gravimetric capacitance was traditionally used as the figure-of-merit to evaluate an EC electrode, the volumetric performance is becoming an increasingly important metric to consider for many practical applications with limited space such as portable electronic products [14][15][16][17][18][19][20] . However, there is usually a trade-off relationship between the gravimetric and volumetric capacitances for most electrode design.…”
mentioning
confidence: 99%
“…By carefully controlling the capillary evaporation-induced drying process, as shown in Fig. 4, Tao et al [59] reported a tightly packed yet porous graphene assembly with a density of 1.58 g cm −3 . In the drying process, the surface tension exerted on the graphene layers led to the shrinking of the assembly, resulting in a compactly compressed yet ion penetrable carbon.…”
Section: Strategies To Improve the Volumetric Performance Of Electrodmentioning
confidence: 99%
“…This inherited the high surface area, excellent conductivity, and flexibility of the graphene and the CNTs and gave a high capacitance of 200 F g −1 [46]. A 3D graphene network deposited with manganese dioxide 1.58 -KOH [147] (MnO 2 ) nanoparticles was constructed on graphene fibers (MnO 2 /G/GF), and an all-solid-state supercapacitor based on this hybrid not only had excellent mechanical flexibility and but also exhibited a high capacitance which was mainly contributed by the EDLC of 3D graphene and the pseudocapacitance of MnO 2 [47]. Graphene-based fibers can also be woven into a network to obtain a film electrode.…”
Section: Graphene Fibersmentioning
confidence: 99%
“…Furthermore, this porous and dense monolith is conductive and moldable, and can therefore be used directly as a well-shaped electrode sheet free of additives, yielding a high device-level energy density for supercapacitors (Fig. 13) [147]. Moreover, by embedding high-capacity non-carbon materials in the void space of the dense graphene matrix, the carbon-non-carbon hybrid delivered high volumetric capacitances even at a high mass loading of active materials and a high current density [83][84][85]116].…”
Section: Further Design and Functionalization Of Graphene-derived Carmentioning
confidence: 99%